2009
DOI: 10.1007/s00127-009-0125-2
|View full text |Cite
|
Sign up to set email alerts
|

Is the implementation of assertive community treatment in a low-income country feasible? The experience of Tbilisi, Georgia

Abstract: High-quality community care costs less than usual treatment and inpatient care and seems to be effective to improve clinical and social outcomes; for these reasons, policymakers should consider, in their future mental health reforms, allocating more resources to community-based care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…Yet, in Lausanne, Switzerland, a retrospective study 6 has shown a positive impact of an ACT program on hospitalization rate and clinical and social outcomes. Also, the establishment of ACT in low‐income countries may be beneficial 7 . These apparently contradictory findings may be related to the characteristics of patients included, and/or to the comparative ambulatory treatments offered, which may in some places be better than the ‘older care’ which was offered as a control treatment in the older trials 5 …”
mentioning
confidence: 99%
“…Yet, in Lausanne, Switzerland, a retrospective study 6 has shown a positive impact of an ACT program on hospitalization rate and clinical and social outcomes. Also, the establishment of ACT in low‐income countries may be beneficial 7 . These apparently contradictory findings may be related to the characteristics of patients included, and/or to the comparative ambulatory treatments offered, which may in some places be better than the ‘older care’ which was offered as a control treatment in the older trials 5 …”
mentioning
confidence: 99%
“…Auch in den letzten Jahren liegt der Schwerpunkt gesundheitsökonomischer Analysen überwiegend in der Bewertung spezifischer gemeindepsychiatrischer Behandlungsformen, insbesondere auf der Basis des ACT-Ansatzes [5,24,39,40], aber auch zur Krisenintervention [9,23] und zur Frühintervention bei Psychoseerkrankungen [22,25]. Aktuelle Studien zur Kosteneffektivität von ACT-Programmen in Großbritannien [4,23,24], Polen [39], Georgien [40] und den USA [5] zeigen, dass diese im Vergleich zur Routinebehandlung in der Regel zu einer Erhöhung der ambulanten psychiatrischen Versorgungskosten führen und dass diese höheren ambulanten Kosten nur dann durch eine gleichzeitige Reduzierung stationärer Behandlungskosten ausgeglichen werden ("cost offset"), wenn es sich bei der Untersuchungspopulation um Patienten mit einem besonders hohen Hospitalisierungsrisiko handelt, wie z.…”
Section: Aktuelle Entwicklungenunclassified
“…Aktuelle Studien zur Kosteneffektivität von ACT-Programmen in Großbritannien [4,23,24], Polen [39], Georgien [40] und den USA [5] zeigen, dass diese im Vergleich zur Routinebehandlung in der Regel zu einer Erhöhung der ambulanten psychiatrischen Versorgungskosten führen und dass diese höheren ambulanten Kosten nur dann durch eine gleichzeitige Reduzierung stationärer Behandlungskosten ausgeglichen werden ("cost offset"), wenn es sich bei der Untersuchungspopulation um Patienten mit einem besonders hohen Hospitalisierungsrisiko handelt, wie z. B. im Fall der von Cusack et al [5] untersuchten psychisch kranken Straftäter.…”
Section: Aktuelle Entwicklungenunclassified
See 1 more Smart Citation
“…The results demonstrated that such a programme could potentially reduce rates of hospitalization, homelessness and imprisonment and increase employment. Another single group pre‐post study of 24 MHC investigated the outcomes of an ICMHS programme in Georgia (Zavradashvili et al, 2010). The results showed that a high‐quality ICMHS was feasible and could cost less than the usual treatment and inpatient care, while apparently improving clinical and social outcomes.…”
Section: Introductionmentioning
confidence: 99%